PENGARUH MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Anggi Fitri; Firdaus Firdaus; Juni Kardi; Yundri Akhyar; Zalisman Zalisman; Syahri Ramadhan (Jurnal Pendidikan, 2021)
This study aims to determine the effect of the Cooperative Integrated Reading and Composition learning model on students' reading comprehension skills. This research uses a quantitative approach with the type of research Quasy Experiment Design. Experimental research is research that is intended to determine whether or not there is a result of "something" imposed on the subject under investigation. In other words, experimental research tries to examine whether there is a causal relationship. The trick is to compare one or more experimental groups that were treated with one or more control groups who did not receive treatment. The data collection instrument was in the form of test questions that were distributed to all research samples. While the research data analysis technique used descriptive analysis, the prerequisite test used the analysis of normality and homogeneity. Meanwhile, to answer the hypothesis results using the Two-Way ANOVA test. The results of the two-way ANOVA test analysis show that a significance value of 0.000 ˂ 0.05 is obtained, it can be concluded that learning using the Cooperative Integrated Reading and Composition model has a significant effect on students' reading comprehension skills.